Accumulation of Viral Transcripts and DNA during Establishment of Latency by Herpes Simplex Virus - Kramer, Martha F. (American Society for Microbiology, 1998)
Latent infection of mice with wild-type herpes simplex virus is established during an acute phase of ganglionic infection in which there is abundant viral replication and productive-cycle gene expression. Thymidine kinase-negative mutants establish latent infections but are severely impaired for acute ganglionic replication and productive-cycle gene expression. Indeed, by in situ hybridization assays, acute infection by these mutants resembles latency. To assess events during establishment of latency by wild-type and thymidine kinase-negative viruses, we quantified specific viral nucleic acid sequences in mouse trigeminal ganglia during acute ganglionic infection by using sensitive PCR-based assays. Through 32 h postinfection, viral DNA and transcripts representative of the three kinetic classes of productive-cycle genes accumulated to comparable levels in wild-type- and mutant-infected ganglia. At 48 and 72 h, although latency-associated transcripts accumulated to comparable levels in ganglia infected with wild-type or mutant virus, levels of DNA accumulating in wild-type-infected ganglia exceeded those in mutant-infected ganglia by 2 to 3 orders of magnitude. Coincident with this increase in DNA, wild-type-infected ganglia exhibited abundant expression of productive-cycle genes and high titers of infectious progeny. Nevertheless, the levels of productive-cycle RNAs expressed by mutant virus during acute infection greatly exceeded those expressed by wild-type virus during latency. The results thus distinguish acute infection of ganglia by a replication-compromised mutant from latent infection and may have implications for mechanisms of latency.